First record of Mesopithecus (Cercopithecidae, Colobinae) from the Miocene of the Iberian Peninsula. Issue 88 (November 2015) - Alba, David M.; Montoya, Plini; Pina, Marta; Rook, Lorenzo; Abella, Juan; Morales, Jorge; Delson, Eric
Abstract: We report dental remains of the extinct colobine monkey Mesopithecus from the Turolian (MN13, Late Miocene, ca. 6.23 Ma) locality of Venta del Moro (Valencia, Spain). They include most of the deciduous dentition and the unerupted germs of the first molars of a single infantile individual, as well as two lower left lateral incisors from two additional individuals. On the basis of morphometric comparisons, mainly based on the M1 s, these remains are attributed to the Late Miocene species Mesopithecus pentelicus . They represent a significant addition to the knowledge of the deciduous dentition of this taxon, much less well-known than the permanent dentition. Although this genus was widely distributed from the Late Miocene through the Pliocene across Europe, southwestern Asia, Pakistan, and China, until now its occurence in the Late Miocene of the Iberian Peninsula had not been documented conclusively. Hence, the reported remains considerably enlarge southwestwards the known geographic distribution of Mesopithecus . The presence of this genus at Venta del Moro must be understood within the framework of the significant faunal turnover that took place in European faunas during the latest Turolian (the second Messinian mammalian dispersal), which is further documented at this locality by the occurrence of other eastern immigrants. At the same time, the presence of M. pentelicus at this site agrees well with previous paleoenvironmental and sedimentological evidence, indicating a lacustrine depositional environment with strong hydrologic seasonality.